Analysis of The Possibility of Price Level Targeting in Indonesia to Achieve Price Stability an Alternative to Inflation Targeting - Eka Budiyanti, Telisa Aulia Falianty (Badan kebijakan Fiskal, 2009)
Price Stability is one of the important macroeconomic policy goals. In recent years, price stability has become an important issue for society, especially since oil and global food price increase continually. This phenomenon motivates this study to know, wheter Inflation Targeting (IT) or Price Level Targeting that more appropriate to apply in Indonesia's monetary framework.IT is ignoring the deviation from past target. The average inflation rate will be convergent to the long term target. Other alternative that has been studied scientifically is Price Level Targeting (PLT). PLT is a policy that has the effect of systematically responding to deviations of the price level from the price level target to preclude long term price level drift.This study will discuss possibility to apply PLT over IT in Indonesia from welfare gain side. The result from theoretical modeling, generally indicate that PLT isbetter to apply than IT. But empirical result using Dittmar, Gavin, and Kydland model (1999) shows that IT is gap hypothesis in indonesia during period of study (1983-2008). The result with secondary data also show that IT has been quite successfully applied consistently. It can be seen by stationary inflation during period of study.